The Intelligent Digital Banking Technology and Architecture: A Systematic Literature Review - Indriasari, Elisa; Prabowo, Harjanto; Lumban Gaol , Ford; Purwandari, Betty (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The digital banking sector has made tremendous progress in user-friendly, efficient, and rapid financial transactions, owing to the exponential growth of ICT technologies. Consequently, many new banking products, services, and business opportunities have emerged. This paper presents a comprehensive analysis of new emerging technologies and architecture that can support the development of intelligent digital banking platforms. The aim of this study is to explore the latest relevant technology to enhance customer experience and minimize human interaction to prevent the spread of COVID-19. The study follows Kitchenham's SLR principles and goes into great depth regarding the process of choosing and analyzing relevant research papers. This research promoted 40 articles that discuss potential emerging technologies, such as artificial intelligence, blockchain, big data, biometrics, and cloud computing. Some key areas of literature were examined, such as technological trends, potential features, and technical solutions. The articles selected were based on specific criteria and used high-quality databases, including IEEE Xplore, Elsevier, SpringerLink, ACM, and AIS. This study considered recent papers published between 2015 and 2021. The mapping study presents digital banking technology and proposes an integrated architecture for developing intelligent digital banking platforms.